Obraz, nieobecność i moment krytyczny (Uwagi o pewnej frazie Jaspera Johnsa) - Leśniak, Andrzej (Przestrzenie Teorii, 2007)
The experience of Minimal Art tells us that a visual object can confront us with absence. The minimal objects are absent - they do not recall any past, they do not refer to any story that might be their source. At least this is the very first impression...But this situation does not make all the utterances concerning these objects impossible. It is rather the opposite - the absence of story, the negation of history is the beginning of another way of writing about art.